A simple and effective evolutionary algorithm for the capacitated location-routing problem - Lopes, Rui Borges (2016)
This paper proposes a hybrid genetic algorithm (GA) to solve the capacitated location-routing problem. The proposed algorithm follows the standard GA framework using local search procedures in the mutation phase. Computational evaluation was carried out on three sets of benchmark instances from the literature. Results show that, although relatively simple, the proposed algorithm is effective, providing competitive results for benchmark instances within reasonable computing time.